The role of salivary biomarker as a diagnostic tool in oral cancer: a literature review - Ni Made Ista Prestiyanti (Intisari Sains Medis, 2020)
Background: Saliva is an informative biological fluid that has gained a lot of interest because of its physiologic diagnostic medium. The recent findings suggest that saliva could be used as a biomarker in diagnosing oral cancer. This study aims to elaborate further on the role of salivary biomarker as a diagnostic tool in oral cancer through literature review.Methods: A total of 44 relevant kinds of literature were studied regarding saliva and oral cancer. The data collection for eligible articles were conducted from 1997 to 2019. Different database and manual search methods were used to find the topic-related articles.Results: The study of saliva as a biological matrix has been identified as a new landmark initiative in search of a useful biomarker to diagnose oral cancer through proteomics and transcriptomics. Most oral cancers are oral squamous cell carcinoma. Using saliva for early oral cancer detection in the search for new clinical markers is a promising approach because of its noninvasive sampling and easy collection method. Identification of this salivary biomarker could help to screen patients at risk, predict disease outcome and effectively contribute to planning treatment strategies.Conclusion: proteomics and transcriptomics molecules on the saliva could be used as a biomarker in diagnosing oral cancer.